Beyond Fintech : Leveraging Blockchain for More Sustainable and Inclusive Supply Chains - Niforos, Marina (International Finance Corporation, Washington, DC, 2018)
One of the most noticeable and important developments of the advance of free trade over the last half century has been the emergence of global value chains. These production and supply networks cross multiple borders and connect advanced and emerging economies. They are vehicles that can deliver on many of the promises of globalization. Yet operating them is complex and costly. Global trade since the great recession has slowed, in part because of a lack of transparency and interoperability within these networks. Blockchain, a technology with unique abilities to record, track, monitor, and exchange assets without need of an intermediary, may be the solution to many of the logistical and cost issues that plague the growth and operation of global value chains, especially in the case of food, agribusiness, and pharmaceuticals. It also has potential to address issues of inclusion.